2022
DOI: 10.21203/rs.3.rs-1944200/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-care behaviours and associated factors among type 2 diabetes patients in Ghana: A systematic review

Abstract: Introduction: Diabetes remains an emerging public health challenge in Ghana. The control of cardio‑metabolic risk factors among type 2 diabetes patients in the country is suboptimal, leading to massive healthcare costs. This systematic review examined the extent of adherence to self-care behaviours and associated factors among type 2 diabetes patients in Ghana.Methods: PubMed, PsycINFO, Scopus, and Google scholar were used to identify quantitative observational studies published between 1990 and June 2022. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
(146 reference statements)
0
4
0
Order By: Relevance
“…This is supported by the work of Suglo et al which found that people are knowledgeable of what constitutes a healthy diet and what foods are suitable for people living with diabetes in Ga Mashie (33); nonetheless, a healthy diet was perceived as expensive, with cost as a major barrier to consumption of healthy food (33). Furthermore, the adherence to self-care behaviours among people living with diabetes is also a challenge as demonstrated by Opoku et al, where the mean number of days per week adherence to dietary recommendations was 3.9-4.4 days/week; and where only 2.7% of people living with diabetes adhere daily to these recommendations (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by the work of Suglo et al which found that people are knowledgeable of what constitutes a healthy diet and what foods are suitable for people living with diabetes in Ga Mashie (33); nonetheless, a healthy diet was perceived as expensive, with cost as a major barrier to consumption of healthy food (33). Furthermore, the adherence to self-care behaviours among people living with diabetes is also a challenge as demonstrated by Opoku et al, where the mean number of days per week adherence to dietary recommendations was 3.9-4.4 days/week; and where only 2.7% of people living with diabetes adhere daily to these recommendations (34).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent self-care among individuals living with diabetes presents notable challenges, reflecting varied adherence levels to medication and care recommendations (34). Barriers to effective self-management are likely to include limited knowledge about diabetes dietary strategies, financial constraints, treatment non-compliance, restricted access to glucometers, inadequate social support, and prolonged waiting times at healthcare facilities (43).…”
Section: Discussionmentioning
confidence: 99%
“…Such patients usually rely on alternative sources of treatment, such as spiritual healing. Mistrust of biomedical forms of treatment coupled with strong beliefs in spiritual or herbal treatment prevents some patients from accessing hospital healthcare [ 6 , 49 ]. Therefore, the findings should be interpreted in the context of the variety of patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…A self-care regimen is a priority approach in diabetes management due to its positive impact on diabetes outcomes [ 5 ]. The findings of a systematic review on self-care behavior in Ghanaians with T2DM show that adherence to a self-care regimen is suboptimal [ 6 ]. Physical activity (PA) is an essential component of a self-care regimen [ 7 ].…”
Section: Introductionmentioning
confidence: 99%